2015
DOI: 10.1007/s11420-014-9398-4
|View full text |Cite
|
Sign up to set email alerts
|

Modern Instrumentation of the Pediatric Occiput and Upper Cervical Spine

Abstract: Background: Rigid screw rod techniques for cervical stabilization are widely used in adults. The benefits of rigid internal fixation include increased fusion rates, improvements in deformity correction, and diminished immobilization requirements. Applications of these techniques in children are challenging due to size constraints and the pathologic conditions encountered which require instrumented cervical fusions. Preparation as well as thorough understanding of the anatomy and surgical techniques is paramoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A few previous studies have evaluated certain anatomical parameters on magnetic resonance imaging (MRI), such as sagittal diameter and lateralization of the cervical spinal cord in healthy volunteers and patients undergoing surgery with cervical conditions such as cervical kyphosis or spondylotic myelopathy. 4,[11][12][13][14][15] Nonetheless, few studies have focused on the preoperative assessment of the spinal cord safety margins in the axis.…”
mentioning
confidence: 99%
“…A few previous studies have evaluated certain anatomical parameters on magnetic resonance imaging (MRI), such as sagittal diameter and lateralization of the cervical spinal cord in healthy volunteers and patients undergoing surgery with cervical conditions such as cervical kyphosis or spondylotic myelopathy. 4,[11][12][13][14][15] Nonetheless, few studies have focused on the preoperative assessment of the spinal cord safety margins in the axis.…”
mentioning
confidence: 99%
“…A study by Odent et al found that patients with odontoid fractures who were treated with a halo device (12 patients) had a better overall recovery and experienced fewer complications compared to those who were managed operatively (three patients) [ 23 ]. Many other studies have found similar results, highlighting the principle that external fixation remains the preferred modality of treatment for pediatric odontoid injuries [ 24 - 26 ]. Of the 10 patients in our study who were stabilized with cervical orthoses, Minerva vest, and Miami J collar braces were utilized.…”
Section: Discussionmentioning
confidence: 57%
“…In cases of severe cervical spine fractures or dislocations, unstable injuries, or progressive deformity, surgical interventions via internal fixation or surgical decompression are warranted as definitive treatment [ 14 , 19 , 25 ]. The innate pediatric cervical anatomy may pose a greater challenge for pin or screw placement when compared to the adult spine [ 26 ]. However, the advent of technological advancements in preoperative and intraoperative imaging has assisted clinicians in discerning the anatomical variations in each patient and ultimately guiding operative management [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Throughout the past 2 decades, rigid fixation techniques have overtaken semirigid techniques for stabilization of craniocervical and subaxial cervical instability, with improved outcomes. [5][6][7] However, large, multicenter, or multidisciplinary studies investigating the surgical outcomes, clinical and radiographic criteria for instability, or the nonoperative management of these patients have been very limited. [8][9][10][11] Originally developed by the RAND Corporation during the Cold War, the Delphi method was first used to predict which American industrial targets might be bombed by the Soviet Union and to determine the quantity of bombs required to damage US munitions.…”
mentioning
confidence: 99%